2001
DOI: 10.1128/aem.67.10.4454-4457.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of ςBin Heat, Ethanol, Acid, and Oxidative Stress Resistance and during Carbon Starvation inListeria monocytogenes

Abstract: To determine the contribution of sigma B ( B ) to survival of stationary-phase Listeria monocytogenes cells following exposure to environmental stresses, we compared the viability of strain 10403S with that of an isogenic nonpolar sigB null mutant strain after exposure to heat (50°C), ethanol (16.5%), or acid (pH 2.5). Strain viabilities were also determined under the same conditions in cultures that had been previously exposed to sublethal levels of the same stresses (45°C, 5% ethanol, or pH 4.5). The ⌬sigB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(194 citation statements)
references
References 25 publications
11
181
1
1
Order By: Relevance
“…While these results may seem surprising, considering the well-documented occurrence in the vacuole of the types of stressful conditions that have been shown to activate s B or to affect survival of a DsigB mutant (e.g. low pH, oxidative stress) (Chaturongakul & Boor, 2004;Ferreira et al, 2001;Maul et al, 1995;Sue et al, 2004), virulence gene expression has been shown to differ between L. monocytogenes present in professional and nonprofessional phagocytes (Bubert et al, 1999). Hence, it is possible that the intravacuolar environment of professional phagocytes is a more stressful environment for intracellular bacterial pathogens than that in other cell types, which may Table 2) detects transcripts covering the plcA coding region; probe 2 ('plcA-readthrough') detects plcA readthrough transcription; probe 3 ('prfA-P1') detects P1prfA transcript including plcA readthrough transcripts; probe 4 ('prfA-CDS') detects all prfA coding region transcripts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While these results may seem surprising, considering the well-documented occurrence in the vacuole of the types of stressful conditions that have been shown to activate s B or to affect survival of a DsigB mutant (e.g. low pH, oxidative stress) (Chaturongakul & Boor, 2004;Ferreira et al, 2001;Maul et al, 1995;Sue et al, 2004), virulence gene expression has been shown to differ between L. monocytogenes present in professional and nonprofessional phagocytes (Bubert et al, 1999). Hence, it is possible that the intravacuolar environment of professional phagocytes is a more stressful environment for intracellular bacterial pathogens than that in other cell types, which may Table 2) detects transcripts covering the plcA coding region; probe 2 ('plcA-readthrough') detects plcA readthrough transcription; probe 3 ('prfA-P1') detects P1prfA transcript including plcA readthrough transcripts; probe 4 ('prfA-CDS') detects all prfA coding region transcripts.…”
Section: Discussionmentioning
confidence: 96%
“…haemolysin production (Freitag & Portnoy, 1994;Nadon et al, 2002), it does not affect L. monocytogenes invasion capabilities in human intestinal epithelial cell lines (Kim et al, 2004(Kim et al, , 2005. In L. monocytogenes, s B also contributes to survival under a variety of lethal environmental stresses (Ferreira et al, 2001), including acidic conditions mimicking mammalian gastric fluid (Chaturongakul & Boor, 2004;Cotter et al, 2001;Wiedmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Overnight broth cultures were diluted 1 : 1000 into 10 ml BHI broth and incubated at 30 uC. When these cultures reached OD 600 =0?4, they were each diluted again (1 : 200) into 120 ml BHI and incubated until each culture reached OD 600 =0?4, as previously described (Ferreira et al, 2001(Ferreira et al, , 2003.…”
Section: Methodsmentioning
confidence: 99%
“…In L. monocytogenes, the gene encoding σ B (sigB) was identified based on its homology to the sigB gene from Bacillus subtilis. Phenotypic characterization of L. monocytogenes strains lacking sigB has shown that σ B plays a role in resistance to various forms of environmental stress, including osmotic, oxidative, and acid stress [16][17][18] . Also, a broad role for σ B -dependent genes in virulence has recently been sug- gested for Gram-positive bacteria.…”
Section: Monocyotogenes In Food Products and Ecosystemsmentioning
confidence: 99%